Data Warehouse Schemas using Multidimensional Data Model for Retail - Kheri Arionadi Shobirin; Adi Panca Saputra Iskandar; Ida Bagus Alit Swamardika (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
A data warehouse are central repositories of integrated data from one or more disparate sources from operational data in On-Line Transaction Processing (OLTP) system to use in decision making strategy and business intelligent using On-Line Analytical Processing (OLAP) techniques. Data warehouses support OLAP applications by storing and maintaining data in multidimensional format. Multidimensional data models as an integral part of OLAP designed to solve complex query analysis in real time.